Rationality, Responsibility, Health Care: Motivation for Childbearing at the Edge of the 21st Century in Russia - Иван Владимирович Забаев (Journal of Economic Sociology, 2011)
The paper presents a study of the motivation for childbearing in contemporary Russia. The research relies on 80 narrative interviews collected in seven Russian cities. Data analysis was performed in accordance with grounded theory techniques. The author questions the theory that suggests the connection between raising rationality of human behavior and decreasing childbearing. The research findings reveal parents’ inclination to grasp childbearing mostly in affective sense. Moreover, the observed participants face the necessity to conquer specific fears tied with uncertainty and doubts about their family’s future. With the only exception of churching (orthodox) respondents, they describe their parenting experience in a rational way. The article explicates the category of “responsibility” as a prime concept used by the respondents to conceptualize childbearing, or more precisely risk-spectrum associated with this decision. Collected interviews highlight the importance of health care institutions and medical discourse that provide substantive meanings for parent’s fears. The author conjectures that health care institutions effect childbearing attitudes in a negative way. Narratives provide a support for this hypothesis: respondents explain low childbirth motivation employing arguments and perceptions adopted from official medicine and the related fields. In conclusion, author argues inspiring family ideology is inherent in religious discourse, while the medical discourse ignores any kind of motivation.